[The Reserve Base, Reserve Requirements, and the Equilibrium Rate of Interest]: Reply - Grossman, Herschell I. (Quarterly Journal of Economics, 1968)
Journal Article The Reserve Base, Reserve Requirements, and the Equilibrium Rate of Interest: Reply Get access Herschel I. Grossman Herschel I. Grossman Brown University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 82, Issue 3, August 1968, Pages 504–507, https://doi.org/10.2307/1879521 Published: 01 August 1968